Implication of Current ASE/EACVI Left Ventricular Diastolic Function Classification in Predicting 2-Year MACE in Asymptomatic Patients with Diabetes and Hypertension. (14th October 2021) - Foo, D; Lam, K H; Igo, M; Sulaiman, M N A; Ku, M Y; King, T L; Yeo, L S; Chunggat, J; Ahip, S S; Sahiran, M F; Mustapha, M; Michael, J; et al.
Abstract: Background: Left ventricular diastolic dysfunction (LVDD) has been shown to be more prevalent in patients with diabetes, and once progress to overt heart failure, carry worse clinical outcomes. Substantial number of patients were classified as indeterminate DF based on the current ASE/EACVI guidelines. The implication of current DF classification in predicting MACE among diabetic patients is not well established. Purpose: To assess prognostic impact of current guidelines-based DF classification, and determine predictors of 2-year MACE based on individual LVDD parameters. Methods: A total of 111 patients with diabetes and hypertension who attended diabetic clinic follow-up at the primary healthcare settings were enrolled. All patients had no prior cardiovascular events, had preserved left ventricular (LV) ejection fraction on echocardiography and sinus rhythm on ECG at screening. Echocardiography was performed to obtain parameters of LV dimensions, LV volumes and LVDD. The 2016 ASE/EACVI guidelines were applied to classify DF. All patients were followed up until 2 years to assess MACE. Results: There were 65 (58.6%) female patients. Mean age was 59.86 (7.45); mean duration of DM was 10.5 (5.41). 80 (72.1%) patients were classified as having normal DF (nDF); 24 (21.6%) patients were classified as indeterminate DF (iDF); 7 patients (6.3%) were classified as LVDD. Patients with LVDD had significantly higher LV mass index (LVMI) (mean 121.72±23.28g/m 2 vs 116.62±24.66g/m 2 in iDF vs 102.50±22.89g/m 2 in nDF); higher left atrial volume index (LAVI) (mean 41.24±10.28ml/m 2 vs 30.55±10.07ml/m 2 in iDF vs 25.75±6.30ml/m 2 in nDF); lower lateral e' velocity (mean 6.35±2.05cm/s vs 7.37±1.73cm/s in iDF vs 8.59±2.13cm/s in nDF); higher septal E/e' ratio (mean 14.89±3.29 vs 12.16±3.99 in iDF vs 9.99±2.35 in nDF); higher average septal-lateral E/e' ratio (mean 14.22±3.77 vs 11.34±3.74 in iDF vs 9.04±2.10 in nDF). Among these 111 patients, 10 patients (9%) reported MACE at 2 years. The risk of 2-year MACE is elevated in both iDF [odds ratio (OR) 3.80, 95% CI 0.87–16.54, p=0.075] and LVDD [OR 7.60, 95% CI 1.11–52.02, p=0.039]. LVMI (OR 1.027, 95% CI 1.004– 1.051, p=0.023), LAVI (OR 1.092, 95% CI 1.017–1.172), and average septal-lateral E/e' ratio (OR 1.276, 95% CI 1.047–1.557, p=0.016) significantly correlated with 2-year MACE. Conclusions: LVDD is correlated with increased MACE at 2 years. LVMI, LAVI and average septal-lateral E/e' ratio were predictors of increased risk of MACE at 2 years. Further investigation with larger sample size is warranted. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ministry of Health Malaysia